A first-principles study of strain tuned optical properties in monolayer tellurium. Issue 71 (17th December 2019) - Wang, Jinjin; Guo, Yanrong; Shen, Hong; Chen, Yu-Yo; Zhang, Rongjun; Zheng, Yuxiang; Chen, Liangyao; Wang, Songyou; Jia, Yu; Chen, Hong-Yi; Su, Wan-Sheng
Abstract : We have theoretically investigated the tunable optical properties of monolayer tellurium under biaxial strain and materials with better performance can be obtained with the application of strain. Abstract : First-principles calculations are employed to study the optical properties of monolayer Te tuned by biaxial strain. Our results demonstrate that monolayer Te has strong absorption in the visible and ultraviolet regions, and that a structural transition occurs between the α-phase and the β-phase under certain strain. In addition, there is significant optical anisotropy in α- and β-Te, while γ-Te shows isotropic characteristics due to their different structural properties. Furthermore, strain has a significant impact on the optical properties. With increasing strain, the real and imaginary parts of the dielectric function exhibit redshift. In addition, the absorption spectrum is more likely to be excited under compressive strain rather than tensile strain in α- and β-Te, while only slight differences are induced in γ-Te. These findings can not only enhance the understanding of two-dimensional tellurium, but also provide an effective way to tune the optical properties for potential application in optoelectronic devices.